Community stressors and coping mechanisms in accessing the health system during a double crisis: a qualitative case study from Yangon Region, Myanmar - Hnin Kalyar Kyaw; Kyu Kyu Than; Karin Diaconu; Sophie Witter (International Journal for Equity in Health, 2023)
Abstract Background Due to the COVID-19 pandemic and political crisis, Myanmar’s health system has suspended routine services while struggling to respond to the pandemic. Many people who need continuous care, like pregnant women and people with chronic illnesses, have been facing challenges in seeking and receiving essential health services. This study explored community health seeking practices and coping mechanisms, including their views on health system stressors. Methods This was a cross-sectional qualitative study based on 12 in-depth-interviews with pregnant people and persons with pre-existing chronic health conditions in Yangon. Sampling was purposive, convenience-based and snowball sampling was also used. The 3-delays framework was used to understand how persons were interacting with and accessing health care services; community and health system stressors and coping mechanisms in relation to COVID-19 were also identified. Results Findings showed that Yangon region was the hardest hit with both the pandemic and political crisis and its health system was greatly affected. People were unable to access essential health services on time. The health facilities were not available to see patients, with serious shortages in human resources, medicines and equipment, resulting in interruption of essential routine services. The prices of medicines and consultation fees, and transportation costs, increased during this period. Limited options for accessing care were available due to travel restrictions and curfews. It became challenging to receive quality care because of unavailable public facilities and private hospitals being costly. Despite these challenges, the Myanmar people and health system have shown resilience. Cohesive and organized family support structures and extended and deep social networks played an important role in accessing health care. At times of emergency, people relied on community-based social organizations for transportation and accessing essential medicines. The health system also showed resilience through establishing new service provision options, such as teleconsultations, mobile clinics, and sharing medical advice through social media. Conclusions This is the first study in Myanmar to explore peoples’ perceptions on COVID-19, the health system and their healthcare experiences during political crisis. Although there is no easy way to cope with this dual hardship, the people and the health system, even in a fragile and shock-prone setting like Myanmar, stayed resilient by developing alternative pathways for seeking and providing health services.